The Criminal Code of Mongolia. The General Part. Crime - V. M. Stepashin (Правоприменение, 2024)
Introduction. In a number of positions, the Criminal Code of Mongolia is recognized as more progressive than the Criminal Code of the Russian Federation. Therefore, it is no coincidence that there is a noticeable increase in the number of publications devoted to legislative decisions of the Criminal Code of Mongolia, which are of undoubted interest in scientific discussions on key criminal law issues.General provisions. The Criminal Code opens with Chapter 1 "General provisions", which sets out the goals, principles of the criminal legislation of Mongolia, the rules of its operation in space and time. The Criminal Code of Mongolia enshrines only three principles: legality, justice and guilt. The law explicitly states that it is not allowed to bring a person to criminal responsibility for opinions or beliefs. The issue of the time of commission of ongoing and ongoing crimes has been resolved. The rules on the statute of limitations of a crime have been moved to this chapter.Crime. The foresight of an act in the criminal law is called an indispensable condition for the recognition of an act and omission as criminal, and, in particular, a careless act. The concepts of a continuing crime and an ideal set of crimes are revealed. Only two categories of crimes are fixed: serious and minor. The form of guilt for the purposes of categorization of crimes in the Criminal Code of Mongolia is insignificant. The very forms of guilt (intent and negligence) are named in art. 2.3. At the same time, intent is not divided into types. TheCriminal Code of Mongolia defines the concept of damage and harm caused by a crime. The chapter ends with the regulations on the unfinished crime.Complicity. It is noteworthy that the form of guilt of the crime committed is not specified in the law. A mediocre performer is a person who has committed a crime by using not only a person who has not reached the age from which criminal responsibility begins, an insane person, but also other persons who have not committed a crime in complicity with the perpetrator and do not realize that a crime is being committed, or livestock or other animals. The perpetrator of a crime is also recognized as a person who inclines another person to commit a crime under the influence of physical or mental coercion.Circumstances precluding the criminality of the act. This institution has found regulation in Chapter 4 of the Criminal Code. It can distinguish significant differences from the Russian Criminal Code in regulating necessary defense, extreme necessity, coercion, reasonable risk, and execution of an order.The procedure, grounds for criminal prosecution and exemption from criminal liability. Chapter 6 contains regulatory requirements that define: (1) signs of the subject of the crime – an individual; (2) general rules for bringing to criminal responsibility and (3) special rules for sentencing; (4) rules for exemption from criminal liability and punishment.Liability of legal entities. Chapter 9, which closes the General Part, is devoted to their responsibility, which defines the grounds for bringing legal entities to criminal responsibility; types of criminal liability; guarantees of its inevitability. The basis for the imposition of punishment is the sole or joint decision of authorized officials representing a legal entity, or actions or omissions committed in the interests of a legal entity that contain signs of an appropriate corpus delicti.Conclusions. Modern Mongolian criminal legislation, while maintaining continuity and honoring legal and cultural traditions, has a qualitative originality. The normative prescriptions proposed in it are of interest to Russian criminal law science and the legislator. Undoubtedly, the experience of Mongolian criminal law regulation can and should be taken into account by the domestic legislator.